The role of health policy in the burden of breast cancer in Brazil - Francisco Winter dos Santos Figueiredo; Tábata Cristina do Carmo Almeida; Débora Terra Cardial; Érika da Silva Maciel; Fernando Luiz Affonso Fonseca; Fernando Adami (BMC, 2017)
Abstract Background Breast cancer affects millions of women worldwide, particularly in Brazil, where public healthcare system is an important model in health organization and the cost of chronic disease has affected the economy in the first decade of the twenty-first century. The aim was to evaluate the role of health policy in the burden of breast cancer in Brazil between 2004 and 2014. Methods Secondary analysis was performed in 2017 with Brazilian Health Ministry official data, extracted from the Department of Informatics of the National Health System. Age-standardized mortality and the age-standardized incidence of hospital admission by breast cancer were calculated per 100,000 people. Public healthcare costs were converted to US dollars. Regression analysis was performed to estimate the trend of breast cancer rates and healthcare costs, and principal component analysis was performed to estimate a cost factor. Stata® 11.0 was utilized. Results Between 2004 to 2014, the age-standardized rates of breast cancer mortality and the incidence of hospital admission and public healthcare costs increased. There was a positive correlation between breast cancer and healthcare public costs, mainly influenced by governmental strategies. Conclusions Governmental strategies are effective against the burden of breast cancer in Brazil.